IMMUNE DEPOSITS IN CUTANEOUS LESIONS OF WEGENER'S GRANULOMATOSIS: PREDICTOR OF AN ACTIVE DISEASE - Chhabra, Seema (Medknow Publications & Media Pvt Ltd, 2011)
A retrospective analysis was conducted of eight cases of Wegener's granulomatosis (WG), who presented with cutaneous lesions. The clinical, immunopathologic and histopathologic features of the cutaneous lesions were reviewed. Antineutrophil cytoplasmic antibody (ANCA) status of the patients was established. When possible, a comparison of immunofluorescence findings of skin biopsies was made with those of renal biopsies taken at the same time. In all except one, systemic and cutaneous disease developed concurrently. On histopathology, leukocytoclastic vasculitis was noted in five patients and features of lupus erythematosus and pyoderma gangrenosum in one case each. Four patients showed immunoglobulin deposits in subepidermal blood vessel walls, while one patient showed granular immune deposits at dermo-epidermal junction only. Immunoglobulin G was the most common immunoreactant detected. C-ANCA/proteinase 3 (PR3)-ANCA was positive in six patients, P-ANCA/myeloperoxidase (MPO)-ANCA in one patient, while one patient did not show ANCA positivity on indirect immunofluorescence. All four renal biopsies showed pauci-immune glomerulonephritis, irrespective of the presence (n=3) or absence (n=1) of immune deposits in the skin biopsy. Skin manifestations are encountered in nearly half of the patients with WG, thus it is important to be familiar with cutaneous histopathologic as well as immunofluorescence findings in WG patients.